The Influence of Work Discipline and Leadership Style on Employee Performance Through Work Motivation - M Syamsul Hidayat; Didin Hikmah Perkasa; Ahmad Badawy Saluy (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine the effect of work discipline and leadership style on employee performance at PT. Kalimutu Mitra Perkasa, with work motivation as a mediating (intervening) variable. This study seeks to understand both the direct and indirect relationships between these variables to support the improvement of human resource strategies in the company. Methodology: This study used a quantitative approach. Data were collected using a structured questionnaire distributed to 45 employees. The study applied Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Result: Work discipline has a positive and significant effect on employee performance, Work discipline also positively and significantly influences work motivation, Leadership style significantly and positively affects employee performance and work motivation, work motivation significantly affects employee performance. These findings confirm that work discipline and leadership style directly influence employee performance and indirectly through work motivation. Conclusions: Work discipline and leadership style significantly influence employee performance, with work motivation serving as an intervening variable that strengthens this relationship. Enhancing motivation through appropriate leadership and employee appreciation can drive better performance. Limitations: The study is limited by its small sample size (45 respondents) and focuses only on one company, which may limit the generalizability of the findings to other organizations and industries. Contributions: This study contributes to the field of human resource management, particularly in understanding how internal organizational factors (discipline and leadership) affect employee performance directly and indirectly through motivation. This study offers practical recommendations for managers and HR practitioners seeking to improve employee outcomes.